ANALISIS INFORMASI DAN PENGEMBANGAN DALAM PENERAPAN APLIKASI CUSTOMER RELATIONSHIP MANAGEMENT KLINIK SEBAGAI PENDUKUNG EDUKASI PENYAKIT TIDAK MENULAR - Avid Wijaya; Prima Soultoni Akbar; Hartaty Sarma Sangkot; Endang Sri Dewi Hastuti Suryandari (Jurnal Pendidikan Teknologi Informasi (JUKANTI), 2023)
The rapid development of digital disruption has driven the healthcare sector to embrace technology as a vital tool in engaging patients as health consumers. In the pursuit of providing better services to patients, clinics now increasingly recognize the need for a system that can effectively connect clinics and patients with the ultimate goal of fostering loyalty in healthcare transactions. This research aims to implement a web-based Customer Relationship Management (CRM) application system in clinics. In the design of this research, a descriptive approach is employed, with a focus on the analysis of the requirements necessary for the implementation of CRM application systems in clinics. The research subjects involve primary care clinics located in the city of Malang, serving as samples that represent diverse clinic contexts. The research instrument used is an interview guide, enabling in-depth data collection regarding user needs and expectations. The proposed implementation of the CRM application also involves an analysis of the extent to which users respond to and accept the application. The initial stage of the research involves information analysis to comprehend the various system requirements in different clinics. Subsequently, the development of systems in these clinics is a key step in enhancing the patient experience and interactions between clinics and patients. It is crucial to closely monitor user feedback on this application, how the application affects interactions between patients and clinics, and how user responses can be interpreted into improvements in a new information system that is more user-friendly. This research will provide valuable insights into how technology and application systems can serve as effective tools in enhancing healthcare services and interactions between clinics and patients.).